Pelatihan Marketing Digital bagi Calon Pekerja Migran Indonesia Menggunakan Dana Bagi Hasil (DBH) Cukai Hasil Tembakau (CHT) - Yusuf, Ramayani; Gunardi , Gunardi; Mulya Mantri , Yaya; Caniago , Fauzi; Hatimatunnisani, Hani; Wiyanto , Wiyanto (Forum Komunikasi Dosen, 2024)
Indonesian Migrant Workers Candidates (CPMI) require additional skills to improve their welfare and productivity while working abroad. Digital marketing training has become one of the solutions to provide entrepreneurial skills digitally. The purpose of this training is to equip prospective PMI with digital marketing skills, particularly in creating marketing kits and managing stores in marketplaces. The training method is conducted face-to-face with a hands-on approach. The materials provided include the creation of a marketing kit and the stages of opening and managing a store on the marketplace platform. The marketing kit is created using the Canva application, which can be easily operated by CPMI. The training participants consist of 25 CPMI who will be dispatched to various destination countries. The training results show that 80% of the participants successfully created a basic marketing kit and 65% of the participants successfully created a marketplace account along with their store content. This training is expected to help prospective CPMI develop side businesses digitally while working abroad or after returning to Indonesia